Mechanisms of Neuroinflammation 2017
DOI: 10.5772/intechopen.68990
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NO/cGMP Signaling on Neuroinflammation: A New Therapeutic Opportunity

Abstract: The nitric oxide/cyclic guanosine monophosphate (NO/cGMP) signaling appears to play a key role in inhibiting neuroinflammation and preventing the activation of a proapoptotic pathway, thereby promoting neural cell survival. In addition, evidence indicates that cGMP/protein kinase G (PKG) pathway is involved in the modulation of glial cell activity. Phosphodiesterase 5 (PDE5), which hydrolyzes cGMP in the inactive form, 5ʹGMP, is present throughout the body and brain and has emerged as a potential therapeutic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 202 publications
(255 reference statements)
0
12
0
Order By: Relevance
“…Cyclic nucleotide phosphodiesterase (PDE) inhibitors had shown their remarkable outcomes in different inflammation associated disorders (Peixoto et al, 2017;Li et al, 2018). The PDE superfamily comprises 11 members (PDE1-11), the common N-terminus to C-terminus structure is profoundly known for their catalytic action on cAMP and cGMP.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic nucleotide phosphodiesterase (PDE) inhibitors had shown their remarkable outcomes in different inflammation associated disorders (Peixoto et al, 2017;Li et al, 2018). The PDE superfamily comprises 11 members (PDE1-11), the common N-terminus to C-terminus structure is profoundly known for their catalytic action on cAMP and cGMP.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments in the mouse model of noise-induced SNHL demonstrated that Pde5 inhibition protected against NIHL [102]. Pde5 inhibition has also been clinically beneficial in reversing deficits in stroke patients [103].…”
Section: Resultsmentioning
confidence: 99%
“…3), with all of them having interactions. It has been reported that GUCY1A1 (guanylate cyclases), which was involved in NO/cGMP/PKG mediated neuroprotection, is activated by nitric oxide and plays a key role in inhibiting neuroinflammation 42 . From this perspective, we infer that the combination of nitrergic and dopaminergic neurons contributes to the regulation of smooth muscle contraction.…”
Section: Discussionmentioning
confidence: 99%